Covert audio recording of the clinical encounter to identify learning needs and exemplary performance in a pediatrics residency program - Justin Salehi; Alan Schwartz; Saul J. Weiner (PLoS ONE, 2026)
Background Physicians-in-training receive feedback based on assessment of their observed clinical skills in both the clinical setting and in simulations. These serve as proxy measures for clinician performance – that is, the application of those skills in routine clinical practice when “no one is watching.” In research employing covert audio recording of internal medicine residents to directly assess clinical performance of one competency, contextualizing care, there is a “skills-to-performance gap,” defined as the difference between what clinicians do when overtly observed compared to when covertly observed. Feedback collected based on covert observation has been shown to improve physician performance in adult medicine practice. This feasibility study tests whether covert assessment with feedback can be operationalized in a pediatric residency program employing a modified protocol adapted for the pediatric setting. Methods Parents of patients cared for by consented residents were recruited in a waiting room to carry a concealed audio recorder into their child’s appointment. Following the encounter, the audio recording was coded using the Content Coding for Contextualization of Care (4C) supplemented by expert opinion to identify additional learning opportunities. Findings were shared with participating residents followed by a second round of data collection. Results Among 50 contextual red flags identified across 38 pre-feedback and 13 post feedback audio recorded visits, residents probed just six of them. Of these, patients revealed four contextual factors. They also revealed four contextual factors without a physician probe. In response to only two of these eight contextual factors, the resident attempt to formulate a contextualized care plan. Feedback opportunities unrelated to contextualization of care were also noted. There was no significant change in resident performance with feedback, although sample size was small. Conclusions Concealed audio recording is a feasible strategy for assessing clinician performance and providing feedback in a pediatric residency program.